The effectiveness of applying the communicative method using the Examples Non Examples strategy to improve the speaking skill of yunior high school students at Dar El-HIkmah Boarding School in Pekanbaru / Fa’aliyah Tathbîqi at-Tharîqah al-Ittishaliyah bi Istirâtijiyah Examples non Examples Litarqiyah Mahârah al-Kalâmi ladâ Talâmizi al-Madrasah at-Tsânawiyah bi Ma’had Dâr el-Hikmah Pekanbaru - Marzal, Delviani; E.Hulawa, Djeprin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
ىذا البحث ىو حبث ذبرييب و يهدف إىل معرفة فعالية تطبيق الطريقة االتصالية إبسًتاتيجية Non Examples Examples لًتقية مهارة الكالم لدى تالميذ ادلدرسة الثانوية دبعهد دار احلكمة االسالمي بكنبارو. و سؤال البحث